EVOLUTION AND BASIC SOURSES OF CATHOLIC CONCEPTS OF THE STATE AND LAW - Лозинець, Н. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is based on philosophical and religious analysis of scientific sources and discusses the evolution of state law.